A mechanism for booms and busts in housing prices - Marten Hillebrand; Tomoo Kikuchi (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2012)
We study an exchange economy with overlapping generations of consumers who derive utility from consuming a non-durable commodity and housing. A banking sector offers loans to finance housing. We provide a complete characterization of the equilibrium dynamics which alternates between an expansive regime where housing prices increase and banks expand loans and a contractive regime associated with decreasing housing values and shrinking credit volume. Regime switches occur even under small but persistent income changes giving rise to large and recurrent booms and busts in housing prices not reflecting changes in fundamentals.
urn:nbn:de:swb:90-283023
Keywords: C62; E32; G21; 330; OLG; Housing prices; Credit volume; Boom-bust scenarios; Regime switching; Immobilienpreis; Wohnimmobilien; Kredit; Immobilienfinanzierung; Konjunktur; Overlapping Generations; Dynamisches Gleichgewicht; Theorie